Transcriptomic, peptidomic, and mass spectrometry imaging analysis of the brain in the ant Cataglyphis nodus. Issue 2 (25th March 2021) - Habenstein, Jens; Schmitt, Franziska; Liessem, Sander; Ly, Alice; Trede, Dennis; Wegener, Christian; Predel, Reinhard; Rössler, Wolfgang; Neupert, Susanne
Abstract: Behavioral flexibility is an important cornerstone for the ecological success of animals. Social Cataglyphis nodus ants with their age‐related polyethism characterized by age‐related behavioral phenotypes represent a prime example for behavioral flexibility. We propose neuropeptides as powerful candidates for the flexible modulation of age‐related behavioral transitions in individual ants. As the neuropeptidome of C. nodus was unknown, we collected a comprehensive peptidomic data set obtained by transcriptome analysis of the ants' central nervous system combined with brain extract analysis by Q‐Exactive Orbitrap mass spectrometry (MS) and direct tissue profiling of different regions of the brain by matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) MS. In total, we identified 71 peptides with likely bioactive function, encoded on 49 neuropeptide‐, neuropeptide‐like, and protein hormone prepropeptide genes, including a novel neuropeptide‐like gene ( fliktin ). We next characterized the spatial distribution of a subset of peptides encoded on 16 precursor proteins with high resolution by MALDI MS imaging (MALDI MSI) on 14 µm brain sections. The accuracy of our MSI data were confirmed by matching the immunostaining patterns for tachykinins with MSI ion images from consecutive brain sections. Our data provide a solid framework for future research into spatially resolved qualitative and quantitative peptidomic changes associated with stage‐specific behavioral transitions and the functional role of neuropeptides in Cataglyphis ants. Abstract : Cataglyphis ants exhibit an age‐related polyethism with very distinct behavioral‐stages. As a result of their role in underlying physiological and developmental processes, signaling molecules like neuropeptides play a crucial role in behavioral transition regulations. Here, we combined transcriptomic and peptidomic analysis to obtain a comprehensive peptidomic data set of the Cataglyphis brain. We further applied imaging mass spectrometry to unmask the spatial distribution of neuropeptides and peptides encodes on different peptide genes on 14 µm thin consecutive brain sections. This work represents the initial step to address the functional peptidomic changes underlying age, stage‐, or/and task‐specific behaviors in a social insect.